Flood risk assessment and channel roughness adjustment modeling in a degraded Baliase River basin, Indonesia - Yumna, Yumna; Sapareng , Sukriming; Nur , Burhanuddin; Soma, Andang Suryana; Akmal , Akmal (Brawijaya University, 2025)
Land degradation in the Baliase River Basin continues to worsen due to increasingly complex hydrological phenomena. This study aimed to evaluate peak discharge as a flood reference for a return period of 2–200 years, estimate channel capacity, determine flood risk status, and simulate hydraulic responses to variations in Manning's n value. Peak discharge calculations use the Nakayasu synthetic unit hydrograph method, with field geometric data modeled using HEC-RAS 6.0 software in a steady-state manner. Four technical scenarios were tested: (1) river normalization, (2) clearing of wild vegetation, (3) bank hardening, and (4) channel deepening/straightening. The analysis results indicate that the Baliase River Basin is generally in critical flood conditions, especially in the downstream and central areas (Stations 6-14). Most river segments are unable to accommodate peak discharges for a repeat period of 2 years. The variation in the n value in each scenario suggests that technical intervention can significantly alter the hydraulic characteristics. Adjusting n values can reduce flood risk, primarily through changes in hydraulic form. Scenario 4 is most effective because it increases the cross-sectional area and hydraulic radius, while Scenarios 1 and 3 contribute by reducing channel roughness. Scenario 2 serves as a support strategy and is ideally combined with other strategies. Priority is given to Scenario 4 in areas where discharge exceeds channel capacity.